2020
DOI: 10.1016/j.bone.2020.115317
|View full text |Cite
|
Sign up to set email alerts
|

The role of gut microbiota in bone homeostasis

Abstract: The gut microbiota (GM) is referred to as the second gene pool of the human body and a commensal, symbiotic, and pathogenic microorganism living in our intestines. The knowledge of the complex interaction between intestinal microbiota and health outcomes is a novel and rapidly expanding the field. Earlier studies have reported that the microbial communities affect the cellular responses and shape many aspects of physiology and pathophysiology within the body, including muscle and bone metabolism (formation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 106 publications
0
78
0
Order By: Relevance
“…The other topic which deserves more attention is HPI-associated dysregulation of gut microbiota [ 239 , 606 , 653 , 654 , 655 , 656 , 657 , 658 , 659 , 660 , 661 , 662 , 663 , 664 , 665 , 666 , 667 ], a phenomenon described also in animal models (infected Mongolian gerbils [ 668 ]) and thought to be due mainly to gut immunopathological/inflammatory responses and suppressed gastric acid secretion following chronic/atrophic gastritis or use of acid-suppressive drugs. Gut dysbiosis by affecting various biological processes contributes to the pathogenesis of OP [ 669 , 670 , 671 , 672 , 673 , 674 , 675 , 676 , 677 , 678 , 679 , 680 , 681 , 682 , 683 , 684 , 685 , 686 , 687 , 688 , 689 , 690 , 691 , 692 , 693 , 694 , 695 , 696 , 697 , 698 , 699 ] as well as to numerous other extra-digestive system diseases associated with OFs [ 700 , 701 , 702 ,…”
Section: Clinical Implications and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other topic which deserves more attention is HPI-associated dysregulation of gut microbiota [ 239 , 606 , 653 , 654 , 655 , 656 , 657 , 658 , 659 , 660 , 661 , 662 , 663 , 664 , 665 , 666 , 667 ], a phenomenon described also in animal models (infected Mongolian gerbils [ 668 ]) and thought to be due mainly to gut immunopathological/inflammatory responses and suppressed gastric acid secretion following chronic/atrophic gastritis or use of acid-suppressive drugs. Gut dysbiosis by affecting various biological processes contributes to the pathogenesis of OP [ 669 , 670 , 671 , 672 , 673 , 674 , 675 , 676 , 677 , 678 , 679 , 680 , 681 , 682 , 683 , 684 , 685 , 686 , 687 , 688 , 689 , 690 , 691 , 692 , 693 , 694 , 695 , 696 , 697 , 698 , 699 ] as well as to numerous other extra-digestive system diseases associated with OFs [ 700 , 701 , 702 ,…”
Section: Clinical Implications and Recommendationsmentioning
confidence: 99%
“…Restoring a balanced gut microbiota is considered as a therapeutic tool for various diseases, including OP [ 695 , 730 , 731 , 732 , 733 , 734 , 735 , 736 , 737 ]. Recent studies showed that probiotic and prebiotic supplementation increases bone density in healthy individuals, protects against primary and secondary OP [ 687 , 695 , 699 , 734 , 738 , 739 , 740 ] and exerts beneficial effects in many other extra-digestive diseases [ 740 ]. However, despite the established impact of the gut microbiota on host (patho-) physiology, the potential roles of HPI- and medications-induced gut dysbiosis is not mentioned in current guidelines for OP.…”
Section: Clinical Implications and Recommendationsmentioning
confidence: 99%
“…Recent studies have revealed the critical role of Th17/Treg balance in the bone loss of PMO [45]. Th17 cells are a subset of proin ammatory T helper cells that potently induce the differentiation of osteoclasts by releasing IL-17A, RANKL, TNF, and IL-6 [46,47], consequently leading to bone destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence reported that gut microbiota were associated with multiple kinds of diseases including colon cancer [32], gestational diabetes [33], type 1 diabetes [34], cardiovascular disease [35] and so on. In addition, biological processes containing diet, weight [36], bone homeostasis [37] and postnatal development were also in uenced by gut microbiota. Most of previous studies about gut microbiota focused on coding genes.…”
Section: Discussionmentioning
confidence: 99%